(untitled) (Marketing Jurnali, 2025)
This article highlights the content, importance, opportunities and specific features of the development of the innovative marketing concepts in green economy, with a focus on sustainable strategies that emphasize green marketing, eco-innovation, circular economy and economic growth. The current study examines the effects of green economy practices through eco-innovation to improve the sustainable performance of manufacturing industries. Moreover, this research also intends to test the moderating effect of circular economy practices on the direct relationship between green market practices and eco-innovation. For each of the concepts of innovative marketing, the article outlines the root causes of related problems, suggests solutions, as well as practical recommendations.